Aerosol composition of the tropical upper troposphere - K. D. Froyd; D. M. Murphy; T. J. Sanford; D. S. Thomson; J. C. Wilson; L. Pfister; L. Lait (Atmospheric Chemistry and Physics, 2009)
Aerosol composition was measured by the NOAA single-particle mass spectrometer (PALMS) aboard the NASA WB-57 high altitude aircraft platform during two Aura Validation Experiment (AVE) campaigns based in Costa Rica in 2004 and 2006. These studies yielded the most complete set of aerosol composition measurements to date throughout the tropical tropopause layer (TTL) and tropical lower stratosphere. We describe the aerosol properties of the tropical atmosphere and use composition tracers to examine particle sources, the role of recent convection, and cirrus-forming potential in the TTL. Tropical dynamics and regional air sources played principal roles in dictating tropospheric aerosol properties. There was a sharp change in aerosol chemical composition at about 12 km altitude coincident with a change in convective influence. Below this level, maritime convection lofted condensable material that generated acidic, sulfate-rich aerosol. These particles contained significant amounts of methanesulfonic acid (MSA) and showed evidence of cloud processes. In contrast, continental convection injected particles and precursors directly into the TTL, yielding a population of neutralized, organic-rich aerosol. The organics were often highly oxidized and particles with oxidized organics also contained nitrate. Above the tropopause, chemical composition gradually changed toward sulfuric acid particles but neutralized particles were still abundant 2 km above the tropopause. Deep continental convection, though sporadic and geographically localized, may strongly influence TTL aerosol properties on a global scale. The abundance of organic-rich aerosol may inhibit ice nucleation and formation of tropopause level cirrus.